Retrosigmoid Transmeatal Approach for Resection of Acoustic Neuroma: Operative Video and Technical Nuances of Subperineural Dissection for Facial Nerve Preservation - Liu, James K.; Dodson, Vincent N.; Jyung, Robert W. (Journal of Neurological Surgery Part B: Skull Base, 2019)
The retrosigmoid (suboccipital) approach is the workhorse for most acoustic neuromas in the cerebellopontine angle. In this operative video atlas manuscript, the authors demonstrate the nuances of the subperineural dissection technique for microsurgical resection of an acoustic neuroma via the retrosigmoid transmeatal approach. The plane is developed by separating the perineurium of the vestibular nerve away from the tumor capsule. This perineurium provides a protective layer between the tumor capsule and the facial nerve which serves as a buffer to avoid direct dissection and potential trauma to the facial nerve. Using this technique during extracapsular tumor dissection helps to maximize the extent of tumor removal while preserving facial nerve function. A gross total resection of the tumor was achieved, and the patient exhibited normal facial nerve function (Fig. 1). In summary, the retrosigmoid transmeatal approach with the use of subperineural dissection are important strategies in the armamentarium for surgical management of acoustic neuromas with the goal of maximizing tumor removal and preserving facial nerve function (Fig. 2).The link to the video can be found at: https://youtu.be/L3lPtSvJt60.
Keywords: retrosigmoid; transmeatal; subperineural; perineurium; acoustic neuroma; vestibular schwannoma